Застосування матричних моделей в маркетингових дослідженнях - Бєлова, Тетяна Геннадіївна; Крайнюченко (Форноляк), Ольга Феодосіївна (My University, 2005)
Розглянуто різновиди матричних моделей, які можуть застосовуватися в маркетингових дослідженнях для досягнення підприємством запланованих цілей: визначення видів діяльності, маркетингових можливостей, становища на ринку, конкурентних переваг тощо. The varieties of matrix models, which can be used in marketings researches for achievement of the planned aims an enterprise, are considered: determination of types of activity, marketings possibilities, position, is at the market, competitive edges and others like that. Strategies the use of which will be instrumental in the increase of efficiency of entrepreneurial activity are recommended.
Keywords: матричні моделі; маркетингові дослідження; стратегії; матричные модели; маркетинговые исследования; стратегии; matrix models; marketings researches; strategies; кафедра маркетингу; кафедра маркетингу